Evaluating Knowledge Management And Business Agility: A Research Of Insights Into Smes Innovation - Antony Sentoso; Evy Rahmawati; Dhita Hafizha Asri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the relationship between Organizational Forgetting (OF), Knowledge Management (KM), Business Agility (BA), and Innovation Performance (IP) in SMEs in Batam's food and beverage sector. In Indonesia, SMEs play an important role in economic growth and community welfare, but SMEs players often face challenges in maintaining innovation amid rapidly changing market dynamics. This study uses a quantitative approach by distributing questionnaires to 270 food and beverage SMEs in Batam City. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results of this study indicate that OF and BA have a significant effect on IP, while KM does not have a significant effect on IP. Furthermore, mediation analysis shows that BA also significantly mediates the relationship between OF and IP, while KM does not play a mediating role. This study emphasizes that the ability of SMEs to release outdated knowledge and adapt quickly to dynamic market changes is more effective than simply relying on the storage of knowledge practices. This study also provides theoretical and practical contributions to SMEs to strengthen competitiveness through the management of organizational forgetting and business agility, as well as to support sustainable innovation, while indicating the need for the development of a more practical role for knowledge management in the context of SMEs in the food and beverage sector.